Improving the early diagnosis of suspected patients with COVID-19: a retrospective study of 106 patients - Xuesong Gao; Di Yang; Zheng Yuan; Yijin Zhang; Hongjie Li; Ping Gao; Xiaomin Liu; Wenshan Zhao; Te Xiao; Yanlin Guan; Guiju Gao; Xuefei Duan (Journal of Infection in Developing Countries)
Introduction: An outbreak of coronavirus disease 2019 (COVID-19) occurred in Wuhan, Hubei Province, China. This study aimed to analyze the clinical and epidemiologic characteristics of patients with COVID-19 to better differentiate the suspected patients in Beijing, China.